Determination of Salt Content in Salted Fish in Pangandaran Area Using Argentometric Titration Method - Lukmansyah, Luki; Ramdani, Riva Aulia (LPPM STIKes Muhammadiyah Ciamis, 2025)
Salted fish is a traditional processed food widely consumed in Indonesia due to its affordability, availability, distinctive flavor, and long shelf life. However, despite its popularity, excessive salt used in preservation can lead to serious health issues such as hypertension, kidney problems, and cardiovascular diseases. Therefore, monitoring the salt content in these foods is essential for public health and food safety. This study aims to determine the sodium chloride (NaCl) levels in three commonly consumed salted fish types jambal roti (Arius thalassinus), layang (Decapterus sp.), and layur (Trichiurus sp.), sold in traditional markets and local traders (UMKM) in Pangandaran. It also evaluates whether these products meet the Indonesian National Standard (SNI 8273 2016), which requires salt levels to be between 12% and 20%. The analysis used the Mohr argentometric titration method, with silver nitrate (AgNO3) as the titrant and potassium chromate (K2CrO4) as the indicator. Samples were prepared by grinding, hot water extraction, and titration to measure salt content. Results showed salt levels ranged from 0.514% to 2.17%, with the highest in jambal roti from UMKM I and the lowest in jambal roti from UMKM II. All samples had salt levels well below the minimum standard of the SNI. These findings suggest that while the products are safe regarding sodium chloride levels, the low salt content may imply inadequate preservation, which could affect product stability and shelf life without other preservation methods. Further research is recommended to assess microbial safety and storage quality of these products.